The effectiveness of an evidence-based workplace substance abuse and substance-related HIV prevention programme within a service industry in Cape Town, South Africa - Burnhams, Nadine Catherine (Department of Public Health and Family Medicine, 2022)
This study tested the effectiveness of a substance abuse and substance-related HIV prevention programme designed for use within a South African workplace setting. The overarching study design used in this study was a clustered RCT which employed seven distinct phases. Phase 1 of the study required determining the effectiveness of programmes to prevent substance abuse and substance-related HIV risks at the workplace through a systematic review. This was followed by the selection of a substance abuse and substance related HIV prevention programme for implementation within a service industry in Cape Town, South Africa. Phase 2 employed a cross-sectional study design for collecting baseline data on substance abuse and substance-related HIV risks. Phase 3 of the study required the effective adaptation of the selected evidence-based substance abuse and substance-related HIV risks prevention programme for application in the workplace. This phase was followed by an outcomes evaluation on the implemented programme. Qualitative in-depth interviews with 8 participants, all senior management in the organization where study was conducted, concluded the study. For the clustered RCT, data were gathered from 325 employees who were employed in two divisions within a local municipality. The Team Awareness (TA) intervention, an eight hour evidence-based programme addressing behavioural risk among employees, was administered to 168 employees in the intervention arm. The 157 employees in the control arm received a one hour wellness talk. Self-report questionnaires were used to gather data on demographic variables, the work environment, policy and EAP service utilisation, substance abuse behaviours, co-worker substance abuse and substance-related HIV risks. Data was analysed using a random effects model accounting for clustering. This study found that alcohol is the more commonly substance abused by persons in this sample. Of the sample surveyed, more than three quarters indicated abuse of alcohol, with only a small proportion of employees reporting drug abuse. Close to a quarter had a positive CAGE score greater than the cut-off :!:2, suggesting hazardous drinking patterns. A third of employees in our sample, who use alcohol, reported engaging in risky sexual practices. The results suggest that employees who received TA showed significant reductions in the risky use of alcohol from baseline to three month follow-up. TA was also found to increase willingness to use the EAP service and improve employee knowledge in relation to workplace substance abuse polices. These findings highlight the need for evidence-based prevention programmes in workplace settings. It further highlights that application of one intervention programme, Team Awareness since TA was found to contribute to reductions in problem drinking and increases help-seeking behaviours. Additionally such prevention programmes create positive attitudes towards policies that regulate substance abuse within the workplace environment. The study makes useful recommendations for research practice and policy to help organisations address the burden of substance abuse.